Respons Gereja Katolik Terhadap Reformasi: Konsili Trente dan Pembaruan Pastoral - Tri Santus Sihombing; Yohanes Wilson B.Lena Meo (Anugerah : Jurnal Pendidikan Kristiani dan Kateketik Katolik, 2025)
The Protestant Reformation, pioneered by Martin Luther in the 16th century, was an important moment in Christian history. This movement emerged as a critique of Catholic Church practices, particularly the sale of indulgences and the abuse of power by clergy, which were considered to deviate from the teachings of the Bible. In response, the Catholic Church convened the Council of Trent. This council not only reaffirmed the teachings of the faith but also tightened spiritual discipline and reformed the internal structure to maintain the unity of the Church. In addition, the Council of Trent also encouraged pastoral renewal supported by religious orders, especially the Society of Jesus (Jesuits), which played a major role in education, missions, and social services. This study analyzes the roots of the Reformation, examines the Council of Trent as the official response of the Catholic Church, and explores the forms of pastoral renewal that emerged afterwards. The results show that although the Protestant Reformation was a major challenge, the Catholic Church's response through the Council of Trent and the pastoral renewal movement succeeded in strengthening Catholic identity and left an important legacy that has influenced the development of the Church to this day.